Person-centered perioperative nursing levels of surgical nurses and factors affecting them: Person-centered perioperative nursing levels of surgical nurses - Yüksel, Hümeyra; Akçoban, Sümeyye (Journal of Surgery and Medicine, 2025)
Background/Aim: There is evidence that effective perioperative care provided by nurses shortens the length of hospital stay, particularly in surgical units. However, studies on the level of perioperative nursing by nurses are limited. This study aimed to analyze the level of person-centered nursing by nurses working in surgical units and the factors affecting them. Methods: This cross-sectional descriptive study was conducted between July and August 2023 through face-to-face interviews with 150 nurses working in surgical units of two government hospitals in Adana and Nevşehir provinces who agreed to participate. Data were collected using the "Nurse Introductory Information Form" and the "Person-Centered Perioperative Nursing Scale (PCPON)". Results: It was found that 52% of the nurses were aware of person-centered care, and 71.3% did not believe that the same care should be applied to each patient. The mean score of the PCPON for nurses working in surgical units was 77.233 (14.62). There was a statistically significant difference between the PCPON scores of nurses working in intensive care units, those who chose the nursing profession willingly, those who willingly worked in surgical units, and those with knowledge of person-centered nursing (P<0.05). Conclusion: This study revealed that nurses working in surgical units demonstrated a high level of person-centered perioperative nursing performance. Factors such as willingly choosing the nursing profession, willingly working in surgical units, and educational status were found to influence perioperative nursing.